Response of soybean to novel bio formulation on growth and yield enhancement in Soybean: Response of soybean to novel bio formulation on growth and yield enhancement in Soybean - G SOMANAGOUDA; SHALINI HUILGOL; R CHANNAKESHAVA; G K NAIDU; HARSHIYA BANU; S R SALKINKOP (Journal of Oilseeds Research, 2023)
A field experiment was conducted in kharif 2021 to assess the response of bioformulations in conjunction with RDF on soybean. Seven treatments comprised of bioformulation combinations of recommended dose of fertilizers in conjunction with BioZn, Bio NPK, Rhizobium + MDSR 14 + 12c, one absolute RDF along with control were analyzed in a randomized block design and were replicated thrice. Maximum yield (2702 kg/ha) was obtained with application of RDF only followed by 75 % RDF + Rhizobium + MDSR 14 + 12c (2563 kg/ha) which signified the yield improvement is possible with combined application of fertilizers and biofertilizers.